Don't Go for Different! Developing Specialized Information Services for Researchers from Distinct Subject Areas - Greifeneder, E.; Bressel, P. (Cataloging & classification quarterly, 2024)
Digital library services are frequently designed for specific user groups with very specific usage needs. This article presents a qualitative comparative analysis of findings derived from six user and usability studies in four different specialized subject information services. Rather than postulating hypotheses regarding variations in needs and behaviors among user groups, this article explores similarities among researchers' requirements for specialized information service portals. The findings suggest that distinct subject areas may no longer require separate information systems tailored to each field's specific needs. With the rise of interdisciplinary research, researchers increasingly favor the adoption of a unified system or multiple systems with consistent operation.